PECULIARITIES OF COPING WITH PROBLEM SITUATION OF STUDENTS OF FORM 4 DURING THE LEARNING PROCESS - Plaude, Alla (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The Aim of the study is the peculiarities of coping with stress situations of students of Form 4 during the learning process. In many studies it is emphasised that the learning environment causes strong stress for a large number of children, which in its turn causes behaviour, emotional and mental problems. The present study analyses the most frequent stress situations, how children cope with them and how the types of coping with stress situations impact the learning results.The results of empirical study demonstrate that 52% of children are of the opinion that the causes for disturbances of mental balance are various physical traumas; problems in learning take up the second place, then follow strained relationships with peers and parents and various emotional experiences related to the situation caused by loss and fear.The strategy of adaptive coping has a positive correlation with the learning result. The strategy of passive behaviour has a negative correlation with the learning success. The correlations obtained in the study confirm also the findings made in other studies that if children don’t know how to use the strategies of adaptive behaviour or compensatory skills which help to solve problem situations, they have lower learning results, which can cause various emotional problems.